Does Consumer’s Level of Education Influence Their Recycling and Environmental Protection Attitudes? Evidence From Croatia - Mandarić, Doroteja; Hunjet, Anica (Naše gospodarstvo/Our economy, 2023)
The empirical link between education and consumption varies depending on contextual factors. Some studies have sought a contemporary understanding of the education-environmental concern connection. Evidence shows that education levels might significantly impact environmental actions. Still, some research shows that the influence of education might not significantly impact green attitudes or depend on various contextual factors. This research explores whether the education level of Croatian consumers statistically influences their attitudes towards environmental care, recycling, and waste disposal. It aims to determine whether there exists a statistically significant difference in attitudes among consumers with varying levels of education. By exploring this relationship, the article aims to shed light on the potential role of education in shaping environmentally friendly behaviours. By addressing this research gap and examining the specific case of Croatia, the article aims to contribute to the broader understanding of how education influences environmental consciousness and action, ultimately contributing to global efforts for a more sustainable future.